2017
DOI: 10.1111/tid.12805
|View full text |Cite
|
Sign up to set email alerts
|

Sinusitis caused by Exserohilum rostratum after cord blood transplantation for myelodysplastic syndrome: A case report and literature review

Abstract: Invasive fungal disease is a serious infectious complication of allogeneic hematopoietic stem cell transplantation (HSCT). Exserohilum rostratum is a species causing phaeohyphomycosis, which rarely causes invasive disease in humans. We treated a case of sinusitis caused by E. rostratum after cord blood transplantation (CBT). A 60-year-old man with myelodysplastic syndrome, who had a medical history of an operation to correct deviation of the nasal septum, developed sinusitis caused by E. rostratum under prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In contrast, solid‐organ transplant susceptibility is largely due to the postoperative immunosuppressive regimen 245 . Cohort studies have reported overall mortality for patients with AIFS after receiving SCT or BMT to be 33% to 100% 52,246,247 . In a case–control study of 46 patients with AIFS, Chen et al.…”
Section: Reversing Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, solid‐organ transplant susceptibility is largely due to the postoperative immunosuppressive regimen 245 . Cohort studies have reported overall mortality for patients with AIFS after receiving SCT or BMT to be 33% to 100% 52,246,247 . In a case–control study of 46 patients with AIFS, Chen et al.…”
Section: Reversing Immunosuppressionmentioning
confidence: 99%
“…245 Cohort studies have reported overall mortality for patients with AIFS after receiving SCT or BMT to be 33% to 100%. 52,246,247 In a case-control study of 46 patients with AIFS, Chen et al concluded that SCT was not an independent prognostic factor of AIFS (p = 0.68). 68 Kennedy et al similarly reported no statistically significant association between BMT and AIFS on univariate analysis (p = 0.68).…”
Section: Posttransplantmentioning
confidence: 99%
“…The members of the heat-tolerant genus Exserohilum are ubiquitous in tropical and subtropical regions. However, less than ten cases of invasive non-allergic sinusitis due to Exserohilum have been described in the literature in haematological patients, who were typically pediatric and from warm areas [ 7 11 ]. In 2012, this fungus was the cause of an outbreak of meningitis associated with contaminated methylprednisolone injections [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, E. rostratum has been described as a phytopathogen; however, an outbreak of fungal meningitis associated with contaminated methylprednisolone injections was reported by the Center of Diseases Control (CDC) in the United States in 2012 [ 9 ], culminating in the death of 8% of patients after 12 months of the diagnostic [ 10 ]. Cases of sinusitis [ 11 ] and keratitis [ 12 ] were also reported. Lately, this species has been successfully used as a model of rabbit meningoencephalitis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%